Perkembangan Usaha Manik – Manik Lamudra.Id - Ikhsanul Ramadhan; Desi Armi Syafitri; Fannisa Mawaddah; Intan Salsabila; Ramdani Bayu Putra (Journal of Management and Social Sciences, 2024)
This research aims to determine the design of bead products, procurement of materials for bead product production and the manufacturing process for bead product production at Lamudra.id. This research uses qualitative methods with data collection techniques in the form of interviews and documentation. The bead craft business is one of the micro businesses in the city of Padang. Seeing the obstacles faced by business actors and the desire to improve and develop the bead craft business, assistance is needed to achieve the desire to improve thebead craft business,namely by providing creativity and innovation training in making bead crafts so that business actors have the skills in making various kinds of bead products. Then another obstacle is that the tools are still simple, so procurement of tools is very necessary to speed up the process of making bead crafts and improve the quality produced. The impact of this service is expected to improve quality and innovation in bead craft products. So it is hoped that business actors will increase their income and become more independent.